Stress and General Manifestations on the Human Body: Array - Mocanu, Lacramioara; Cărăuș, Ancuta Loredana (New Trends in Psychology, 2021)
Today, stress has become an increasingly widespread phenomenon. Stress is seen as a response to a situation where individuals are unable to meet the requirements required of them. Occupational stress is not only pressure in the workplace, it is a life-long factor and must be viewed from several perspectives: work load, workplace relationships, organizational structure and climate, role ambiguity and conflict of role, opportunities for career development, work-family relationship. In general, occupational stress is caused by several factors, which can be classified into three groups: external factors, factors that depend on the organization and factors that depend on the employee. Stress can manifest itself in different ways. Symptoms of stress can be divided into three main groups: physiological, psychological and behavioral.